2017
DOI: 10.4049/jimmunol.1600777
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Classification and Functional Characterization of Human Airway Macrophage and Dendritic Cell Subsets

Abstract: The respiratory system is a complex network of many cell types, including subsets of macrophages and dendritic cells that work together to maintain steady-state respiration. Due to limitations in acquiring cells from healthy human lung, these subsets remain poorly characterized transcriptionally and phenotypically. We set out to systematically identify these subsets in human airways by developing a schema of isolating large numbers of cells by whole lung bronchoalveolar lavage. Six subsets of phagocytic antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(113 citation statements)
references
References 91 publications
(138 reference statements)
7
95
3
Order By: Relevance
“…Furthermore, blood cDC2 can be induced to express high langerin and Birbeck granules in response to transforming growth factor‐ β (TGF‐ β ) in vitro although it remains unknown whether cDC2 have any potential to form LC in vivo . Myeloid cDC2 have also been described in the lung, intestine and liver of humans . In the lymph node, most interdigitating cells of the T‐cell areas have a phenotype compatible with cDC2 lineage .…”
Section: Irf4/klf4/notch2‐dependent Myeloid Cdc2mentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, blood cDC2 can be induced to express high langerin and Birbeck granules in response to transforming growth factor‐ β (TGF‐ β ) in vitro although it remains unknown whether cDC2 have any potential to form LC in vivo . Myeloid cDC2 have also been described in the lung, intestine and liver of humans . In the lymph node, most interdigitating cells of the T‐cell areas have a phenotype compatible with cDC2 lineage .…”
Section: Irf4/klf4/notch2‐dependent Myeloid Cdc2mentioning
confidence: 99%
“…Populations of monocyte‐derived cells exist in human steady‐state tissues, including the skin, lung and intestine . It is not known if this is a distinct mechanism of recruitment or one that is accelerated and activated in inflammation.…”
Section: Monocyte‐derived Inflammatory DCmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, CD64 and MAR-1 are considered to be the most selective markers for the effective separation moDC from cDC. In addition to that, the GenChip technology application to DC research has recently demonstrated that DC subsets display different transcriptional factor's requirement in their development and function [7,8]. Several transcription factors including PU.1 (E26 transformation-specific family transcription factor), Bcl11a (C2H2 type zinc-finger protein), Irf4 and Irf8 (Interferon Regulatory Factors 4 and 8, correspondingly), E2-2 (basic helix-loop-helix transcription factor E protein), Id2 (Inhibitor of DNA…”
Section: Subtypes Phenotypes and Functionsmentioning
confidence: 99%